(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is very difficult to imagine our modern life without data. As new technologies and data volume increase, sending them quickly is becoming one of the most important issues. Compression methods are commonly used to transfer data faster when transmitting data. Image compression is one of the data compression types used to compress digital images, to reduce their cost for storage or transmission. In this paper, we propose double compression based low bandwidth video transmitter. The device is capable of transmitting data two-stage compression. The first stage is compression based on the existing interpolation method. In the second stage, it is compressed based on the JPEG method. The relationship between bandwidth and quality in image transmission is also analyzed.